198k views
4 votes
Fill in the value of the function, when the input is 2: y = −4 + 2

User Saneshark
by
5.6k points

2 Answers

4 votes

Answer:

y=-6

Explanation:

y=-4(2)+2

y=-8+2

y=-6

(2,-6)

User Tharindlaksh
by
5.7k points
5 votes

Answer:

y = - 6

Step-by-step explanation: You have to substitute 2 for x in order for you to get your solution.

y = - 4x + 2

y = - 4(2) + 2

y = - 8 + 2

y = - 6

  • Remember, a negative times a positive, becomes a negative

Hope this helps you!!! :)


User Mnemenaut
by
5.1k points